The end of the present world and the mysteries of the future life. - Arminjon, Charles, sac., 1824-1885 (Sophia Institute Press, 2008)
Signs of the end of the world -- Persecution by the antichrist -- Resurrection of the dead and the general judgment -- Place of immortal life or the state of glorified bodies -- Purgatory.